The efficacy of theophylline in preventing cisplatin-related nephrotoxicity in patients with cancer. (27th May 2016) - Karademir, Lutfiye Derya; Dogruel, Fatma; Kocyigit, Ismail; Yazici, Cevat; Unal, Aydin; Sipahioglu, Murat Hayri; Oymak, Oktay; Tokgoz, Bulent
Abstract: Objective : Cisplatin is a potent antineoplastic agent used and its major limiting side effect is nephrotoxicity. The aims of the study are early detection of acute kidney injury (AKI) with biomarkers and investigation of the potential nephron-protective effects of theophylline.Methods : Glomerular filtration rates (GFR), neutrophil gelatinase-associated lipocalin (NGAL), cystatin C were measured at 5th day of treatment in all of the patients. In addition, these parameters were measured repeatedly after the administration of cisplatin, at 2nd hour, 5th and 20th days.Patients : Sixty patients who are planned to receive cisplatin for the first time were included in the study. Patients were divided into two groups as Group 1 ( n = 30) (standard treatment arm) and Group II ( n = 30) (theophylline arm).Results : In both groups after the administration of cisplatin, GFR showed a significant decrease within time ( p = 0.006). Urine NGAL levels were significantly high after 2 h of cisplatin administration ( p < 0.001), no significant difference was observed between groups. However, when the time*group effects were considered together, higher NGAL levels were detected in the group not receiving theophylline ( p = 0.025). After 5 days of cisplatin administration, urine protein levels were significantly higher in both groups ( p < 0.001).Conclusion : Results showed that urine NGAL level is a superior biomarker compared to serum creatinine and serum cystatin C in the detection of early AKI. Theophylline was found not to bring a complete protection for the kidneys, but less nephrotoxicity was developed when compared to the group not receiving theophylline.